2010
DOI: 10.1007/s11104-010-0502-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling root plasticity and architectural ground rules in tree root growth models with voxel automata

Abstract: Dynamic models of tree root growth and function have to reconcile the architectural rules for coarse root topology with the dynamics of fine root growth (and decay) in order to predict the strategic plus opportunistic behaviour of a tree root system in a heterogeneous soil. We present an algorithm for a 3D model based on both local (soil voxel level) and global (tree level) controls of root growth, with development of structural roots as a consequence of fine root function, rather than as driver. The suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
(46 reference statements)
0
27
0
Order By: Relevance
“…This simplification could partly explain the model overestimation of SOC stocks in the 0.0-0.1 m layer of the alleys compared to observed data. This result suggests that it could be useful to couple the CAR-BOSAF model with a model describing root architecture and root growth (Dunbabin et al, 2013;Dupuy et al, 2010), for instance using voxel automata (Mulia et al, 2010). Moreover, the model described a slight increase in SOC stocks in the middle of the alleys rather than close to the trees in the alleys.…”
Section: Representation Of Soc Spatial Heterogeneity In Agroforestry mentioning
confidence: 95%
“…This simplification could partly explain the model overestimation of SOC stocks in the 0.0-0.1 m layer of the alleys compared to observed data. This result suggests that it could be useful to couple the CAR-BOSAF model with a model describing root architecture and root growth (Dunbabin et al, 2013;Dupuy et al, 2010), for instance using voxel automata (Mulia et al, 2010). Moreover, the model described a slight increase in SOC stocks in the middle of the alleys rather than close to the trees in the alleys.…”
Section: Representation Of Soc Spatial Heterogeneity In Agroforestry mentioning
confidence: 95%
“…Still, to a considerable extent, secondary thickening of transport roots occurs in response to, and in coordination with fine branch root development, so the branching pattern present at any time is likely to contain more regularity and predictability than one would expect from the way it is formed. Mulia et al (2010) showed that a dynamic fine root response to local uptake conditions can be reconciled in model algorithms with an emerging fractal branching architecture for woody roots.…”
Section: B Test Of Fractal Branching Assumptions (Also Seementioning
confidence: 99%
“…Alternative approaches to explicitly accounting for root system architecture, e.g. continuous (Dupuy et al 2010) or voxel automata (Mulia et al 2010) approaches, also bear promises, especially when aiming at coupling such models with models of root functioning, integrating root-soil interactions occurring in the rhizosphere. The surface of uptake of a root is not only depending on root system architecture, whatever the level of accuracy of its representation in plant nutrition models.…”
Section: Why and Which Plant Nutrition Models What For?mentioning
confidence: 99%
“…In addition, root system architecture is characterized by a tremendous plasticity (e.g. Hodge 2009;Hodge et al 2009;Mulia et al 2010;Pagès 2011). At a biophysical point of view, excess water (actually limited aeration) and mechanical constraints such as hard pans, rock fragments, etc.…”
Section: Root Segment Modelmentioning
confidence: 99%